Does fetoscopic or open repair for spina bifida affect fetal and postnatal growth?. (5th March 2019) - Sanz Cortes, M.; Davila, I.; Torres, P.; Yepez, M.; Lee, W.; Guimaraes, C. V.; Sangi‐Haghpeykar, H.; Whitehead, W. E.; Castillo, J.; Nassr, A. A.; Espinoza, J.; Shamshirsaz, A. A.; et al.
ABSTRACT: Objective: The effect of fetoscopic myelomeningocele (MMC) repair on fetal growth is unknown. Fetal surgery itself and/or exposure to a carbon dioxide (CO2 ) environment during spina bifida repair may affect placental function and impair fetal growth. Our aim was to assess and compare growth in fetuses, neonates and infants who underwent prenatal fetoscopic or open MMC repair. Methods: Fetal biometrics were obtained serially using ultrasound after fetoscopic ( n  = 32) or open hysterotomy ( n  = 34) MMC repair in utero at a single institution between November 2011 and July 2017. Measurements obtained during growth scans on initial evaluation prior to surgery, and those taken at 6 weeks post‐surgery, were transformed into percentiles and compared between groups. Additional neonatal and infant anthropometric measurements, including weight, length/height and head circumference, were also transformed into percentiles and compared between the groups. The proportions of cases in each group with estimated fetal weight (EFW) or postnatal weight < 10 th and < 3 rd percentiles were calculated and compared. A linear mixed model was used to analyze the serial fetal growth measurements of each parameter, and random intercepts and slopes were used to compare study variables between the study groups. The duration of surgery (skin‐to‐skin time at fetoscopic and open MMC repair) and duration of CO2 exposure (fetoscopic repair) were evaluated for any effect on the fetal, neonatal or infant biometric percentiles. Results: Fetuses which underwent fetoscopic repair had a larger abdominal circumference percentile at referral (57 ± 21 vs 46 ± 23; P  = 0.04). There were no other differences between the two groups in fetal biometric percentiles at the time of referral, 6 weeks post‐surgery or at birth. There were no differences between groups in EFW percentile or in proportions of cases with birth weight < 10 th and < 3 rd percentiles. Linear mixed‐model analysis did not show any significant differences in any fetal growth parameter between the groups over time. There were no significant correlations between duration of surgery or duration of CO2 exposure and any of the biometric percentiles evaluated. Postnatal growth showed no significant differences between the groups in weight, height or head circumference percentiles, at 6–18, 18–30 or > 30 months of age. Conclusions: Babies exposed to fetoscopic or open MMC repair in‐utero did not show significant differences in fetal or postnatal growth parameters. These results support the safety of the use of CO2 gas for fetoscopic surgery. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.